A biomechatronics-based EPP topology for upper-limb prosthesis control: Modeling & benchtop prototype. (March 2022) - Mablekos-Alexiou, Anestis; Kontogiannopoulos, Spiros; Bertos, Georgios A.; Papadopoulos, Evangelos
Highlights: A contemporary Extended Physiological Proprioception control scheme for below the elbow amputations. Experimental evaluation of the proposed control strategy using a benchtop prototype. Feasibility and materialization potential of the proposed scheme is indicated. Abstract: This article reintroduces the concept of Extended Physiological Proprioception (EPP) for below the elbow amputations, eliminating the use of a harness, cineplasty, or Bowden cables, and proposing instead a contemporary scheme inspired by teleoperation theory and its applications. A biomechatronics-based master/slave topology is developed to provide EPP-equivalent control using implanted micro servo actuators directly attached to amputee's residual muscles and wirelessly communicating with the prosthesis. A Position-Force (P-F) control architecture guarantees the dynamic coupling of the actuating muscles with the prosthetic limb, enabling amputee kinesthetic sense. Simulations and Hardware in the Loop (HIL) preliminary experiments with an able-bodied individual are conducted and provide an evaluation of the proposed teleoperation scheme in terms of control transparency and time delay with promising results. An initial feasibility analysis on implants size and power demands based on specific performance criteria, is encouraging, while the materialization potential of the topology is assessed.